Kepastian Hukum Klausula Pengesampingan Pasal 1266 dan Pasal 1267 KUHPerdata terhadap Pembatalan Perjanjian yang Disepakati Para Pihak dalam Akta Notaris - Atpasila, Muh Nur Arisakti; Sahril, Iran; Martanti, Yurisa (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Some business people objected because of the uncertainty of the time for the settlement of default disputes in Court. Therefore, there is often a clause in the agreement for the waiver of Article 1266 and Article 1267 of the Civil Code to cancel the agreement without a court process. The main point of this research discusses the Legal Certainty of the Exclusion Clause of Article 1266 and Article 1267 of the Civil Code in Connection with the Cancellation of the Agreement Agreed by the Parties in the Notary Deed. This study aims to find out the existence of dispute resolution in the Court where the parties have agreed to waive the provisions of Article 1266 and Article 1267 of the Civil Code and the legal certainty of the waiver of the provisions of Article 1266 and Article 1267 of the Civil Code agreed upon by the parties in the Notary Deed. The method used in this study is normative juridical research, namely research on literature law or secondary data with sources of primary, secondary and tertiary legal materials. The research approach used is an analytical approach and the technique of collecting legal materials is carried out by inventorying positive legal rules, literature, books, journals and other sources of legal materials. The analysis technique of legal materials is carried out by carrying out grammatical, systematic, and legal construction methods. The results of the study show that the waiver of the provisions of Article 1266 and Article 1267 of the Civil Code in the Notary Deed that has been agreed upon by the parties, then at the stage of its implementation, there is one of the parties who objects to the waiver of Article 1266 and Article 1267 of the Civil Code in reality can file a lawsuit with the Court in connection with the waiver clause of Article 1266 and Article 1267 of the Civil Code, while the party in the position of the defendant who postulated in his execution that the plaintiff did not have legal standing/persona standi in judicio because he had agreed to waive Article 1266 and Article 1267 of the Civil Code, the reality was not considered by the Court. Article 1266 and Article 1267 of the Civil Code are suggested to be amended by adding an exception sentence in the form of "can be set aside as long as agreed by the parties".